RESEARCH OF THE PERFORMANCE OF SOCIAL PROCESSES ON THE EXAMPLE OF REGISTRATION OF ENROLLEES FOR STATE EXAMS - I. V. Kovalenko; S. A. Pottosina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
This paper describes new applying of Multiple-Valued Logic for estimation of the factors affecting the operation of socio-economic systems, the example of the process of registration of enrollees for state exams by building structure function. It was suggested the algorithm for the study of factors affecting the performance of the social proccess. The practical significance is in the implementation of procedures to assess the significance of factors affecting the performance of the process holding records for centralized testing.